2017
DOI: 10.1164/rccm.201704-0814oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Infections in the Elderly Lead to Impaired Neutrophil Targeting, Which Is Improved by Simvastatin

Abstract: Rationale: Dysregulated neutrophil functions with age and sepsis are described. Statins are associated with improved infection survival in some observational studies, but trials in critically ill patients have not shown benefit. Statins also alter neutrophil responses in vitro.Objectives: To assess neutrophil migratory accuracy with age during respiratory infections and determine if and how a statin intervention could alter these blunted responses.Methods: The migratory accuracy of blood neutrophils from young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 44 publications
(37 reference statements)
2
79
0
Order By: Relevance
“…Furthermore, a number of neutrophil phenotypes have been identified in different experimental models, and these phenotypes seem to display different functional characteristics. For example, neutrophils have been described as senescent15 and immunosuppressive16 (thought to potentially contribute to the immunosuppression seen after sepsis17) although the physiological and pathological relevance of these phenotypes is as yet unclear. A neutrophil phenotype of potential relevance to the current study8 is the so-called ‘angiogenic neutrophil’; a subset which makes up 3% of neutrophils, identified by being CD49d + VEGFR1 high CXCR4 high and characterised by increased MMP-9 release 18…”
mentioning
confidence: 99%
“…Furthermore, a number of neutrophil phenotypes have been identified in different experimental models, and these phenotypes seem to display different functional characteristics. For example, neutrophils have been described as senescent15 and immunosuppressive16 (thought to potentially contribute to the immunosuppression seen after sepsis17) although the physiological and pathological relevance of these phenotypes is as yet unclear. A neutrophil phenotype of potential relevance to the current study8 is the so-called ‘angiogenic neutrophil’; a subset which makes up 3% of neutrophils, identified by being CD49d + VEGFR1 high CXCR4 high and characterised by increased MMP-9 release 18…”
mentioning
confidence: 99%
“…A recent study showed that infections in older adults were associated with prolonged, impaired neutrophil migration. Simvastatin improves neutrophil migration in vivo in healthy individuals and in vitro in milder infective events but not in severe sepsis, supporting its potential utility as an early intervention during pulmonary infections [27,28].…”
Section: Discussionmentioning
confidence: 91%
“…Statins, hydroxymethylglutaryl‐CoA reductase inhibitors, may have effects on inflammatory diseases such as sepsis and ARDS via its multiple properties, including an anti‐inflammatory effect and inhibition of leucocyte adhesion . Statins have become a controversial treatment for sepsis and infectious diseases in recent years . Due to the poor water solubility and strong fat solubility of statins, NP carrier systems have been designed to enhance drug delivery, and it has been confirmed that SV‐NPs have good efficacy towards chronic inflammatory disorders such as atherosclerosis and chronic pulmonary disease .…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Statins have become a controversial treatment for sepsis and infectious diseases in recent years. [36][37][38][39][40] Due to the poor water solubility and strong fat solubility of statins, NP carrier systems have been designed to enhance drug delivery, 41 and it has been confirmed that SV-NPs have good efficacy towards chronic inflammatory disorders such as atherosclerosis and chronic pulmonary disease. 29,42 The formulation of SV-NPs improves the pharmacokinetic profile and bioavailability of SV 43 ; it was also reported that nanostructured lipid carriers, especially those associated with SV, were able to reduce cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%